2013
DOI: 10.1111/jasp.12077
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of long‐distance relationships: the effects of psychological distance between service provider and consumer on the efforts to recover from service failure

Abstract: This paper presents a model of the effects of recovery level in terms of distributive, procedural, and interactional dimensions on consumer attitudes (satisfaction and trust) and their subsequent effects on behavioral intentions. Service medium (online and offline) is considered as a moderating variable in the perspective of psychological distance. Findings reveal that the effects of recovery levels on satisfaction and trust are greater in the offline medium than in the online medium. Moreover, in both low and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 116 publications
(164 reference statements)
0
20
0
1
Order By: Relevance
“…To be more specific, the staffs' smile service influences customer satisfaction by affecting the evaluation of service quality. High-rating service predicts how content customers feel about the service, and online customer service with an e-smile can improve customer satisfaction by improving customer service quality [49]. In light of the above studies, this study proposes hypothesis as below:…”
Section: Research Model and Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…To be more specific, the staffs' smile service influences customer satisfaction by affecting the evaluation of service quality. High-rating service predicts how content customers feel about the service, and online customer service with an e-smile can improve customer satisfaction by improving customer service quality [49]. In light of the above studies, this study proposes hypothesis as below:…”
Section: Research Model and Hypothesismentioning
confidence: 98%
“…Though Darley [48] points it out that factors influencing customers' satisfaction in off-line condition does not suit online context, Huang and Yen's [29] study demonstrates that the use of emoticons in online interaction could help service workers to convey personal feelings to customers and to increase the intensity of text message expression, consequently making individualized service possible. Moreover, studies completed by Lii and Chien [49] indicate that online service workers have to be more engaged than their off-line counterparts. In terms of existent literature, this study proposes hypothesis as below:…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Emotional responses can be described in terms of whether the expression of the apology contains the speaker's sincerity, genuineness, remorse, regret or guilt, and it is always performed non-verbally, such as through facial expressions, signs of fear, and stance [53]. However, in the online recovery context, remote communication makes it difficult to show the emotional response of the apology non-verbally [7], and the asymmetric relationship between the customer service demand and supply also causes the customer to question the emotional response of the service staff's apology [15]. Thus, which form of expression can better show the emotional response to the customer is an important issue in online recovery.…”
Section: Apology Speech Actsmentioning
confidence: 99%
“…Past studies in online recovery indicated that the recovery strategies in offline recovery, such as tangible recovery strategies (e.g., compensation, discounts) [5,6] and intangible recovery strategies (e.g., apologies, empathy, politeness) [4], are likely to be highly applicable in online recovery [2,7]. However, customer participation, which is an important and novel offline recovery strategy to enhance customers' perceived justice and post-recovery satisfaction, has largely been overlooked in the online recovery context [2].…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of this involves understanding how customers represent, that is construe, information about a service and considering how information can be aligned with this construal. In recognition of this, research in marketing and management has examined the importance of psychological distance in different settings (see Dhar and Kim, 2007 for a review) including designing service guarantees (Jin and He, 2012) and responding to service failure (Lii, Chien, Pant and Lee, 2013).…”
Section: The Importance Of Psychological Distance In Service Contextsmentioning
confidence: 99%